Evaluation of Sella Turcica Bridging and Morphology in Different Types of Cleft Patients - Alam, Mohammad Khursheed; Alfawzan, Ahmed Ali (Frontiers in Cell and Developmental Biology, 2020)
Objectives: To evaluate sella turcica (ST) bridging, associated anomalies, and morphology, in subjects with 4 different types of clefts, and compare them with non-cleft (NC) subjects. Material and Methods: A total of 123 (31 NC and 92 cleft) Saudi subjects who had their lateral cephalogram (Late. Ceph.), orthopantomogram (OPG), and clinical details for ordinary diagnosis were included in the study. Among 92 cleft subjects, 29 had bilateral cleft lip and palate (BCLP), 41 had Unilateral cleft lip and palate (UCLP), 9 had unilateral cleft lip and alveolus (UCLA) and 13 with unilateral cleft lip (UCL). ST bridging and 7 parameters related to ST morphology and skeletal malocclusion were analysed using Late. Ceph. Associated dental anomalies in ST bridging subjects were investigated using OPG. The images were investigated using artificial intelligence-driven Webceph software. Multiple statistical tests were applied to see the differences between gender and among cleft versus NC subjects. Results: ST bridging was found to be higher in cleft subjects (22.82%). Most of the cleft subjects had severe skeletal Class III malocclusion associated with multiple types of dental anomalies (impacted canines, congenital missing, and presence of supernumerary teeth). No significant gender disparities in all 7 parameters of ST morphology were found between NC and cleft groups. However, there were significant differences when compared among 4 different types of cleft individuals versus non-cleft subjects. Conclusion: ST bridging is more prevalent in cleft subjects along with Class III malocclusion and associated dental anomalies. ST morphometry differs significantly between cleft versus NC subjects. BCLP exhibits smaller values of all 7 parameters as compared to all other groups.